AROUND A GAZAVAT-NÂME HZ. ALİ’S PLACE IN PEOPLE’S IMAGINATION - Mehmet GÜMÜŞKILIÇ (Fırat University, 2019)
Hz. Ali has left great impact on Muslims. Hz. Ali also bears a very distinctive place in the imagination of Turkish people. He was loved by both Sunnis and Alevis, and his valor has been told for centuries. Among the companions of the Prophet Muhammed, he came first when heroism is mentioned. Cenk-nâme or gazavat-name, a kind of epic poetry, is a literary form that primarily revolves around Hz. Ali, Hz. Muhammed or other imaginary characters that the poets created. The evetns generally take place between Muslims or Christians or non-believers. These works narrate events in a magical, fabulous way; sometimes in an extraordinary manner that is impossible to happen. As they are addressed to common people, they were written in simple language. Cenk-nâmes are also present in Arbabic and Persian literature. The first examples of Cenk-nâmes in Turkish literature were written in the early 14th century. In this essay, some of the legendary characteristics of Hz. Ali, who has left great impact on our people’s imagination and whose stories has been told over and over for centures, took shape around Cumhur-nâme, the work of Tursun Fakih, who had great contributions in the formation of Otttoman State will be shown. By making quotations from this work, the importance of Hz. Ali in our imagination will be presented.